Dendara : la porte d'Horus - Cauville, Sylvie, (Institut français d'archéologie orientale, 2021)
"The Horus Gate brings to a close the two-thousand-year-old cycle which saw Edfu and Dendara united by the closest religious ties. The domain to which it gave access constitutes an enclave within the southern city (Edfu). Horus joins Hathor, and both celebrate Osiris Pa-Akhem, in whose quadruple spirit are subsumed Re, Sokar, Horus, and Osiris. The texts indicate that the Osirian workshop was located in the domain of Horus; from there, the processions went to the Osirian necropolis, the site where the mysteries of Khoiak were performed at Dendara. Completely unpublished until now, the texts and representations from the Horus Gate, decorated in the names of Antoninus Pius (138-161 AD) and Marcus Aurelius (161-180 AD), constitute the final priestly production from a city already flourishing in the Old Kingdom."--Page 4 of cover.